2022
DOI: 10.1002/cctc.202200476
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Promotion Effects of Nb on Alkali Resistance of FeVO4/TiO2 Catalysts for NOx Reduction

Abstract: FeVO 4 -based catalysts with a wide temperature window and high SO 2 tolerance have attracted increasing attention for the selective catalytic reduction of NO x with NH 3 . However, the alkali-resistance of FeVO 4 -based catalysts is still challenging. In this study, the K-resistance of FeVO 4 /TiO 2 was markedly improved via the Nb modification. It was demonstrated that the adsorption and reactivity of NH 3 /NH 4 + and NO x species on K poisoned FeVO 4 /TiO 2 both decreased, which restrained the process of La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The introduction of niobium effectively enhances the surface acidity and alkali-resistance, thereby making niobium oxides a commonly employed modifier for facilitating the NH 3 -SCR reaction. 21 Our group previously found that the intense V–Nb–Ti interaction present in the 1V/Nb 0.15 Ti 0.85 catalyst is conducive to the low-temperature NH 3 -SCR activity. 22 Therefore, in this study, an NbTi composite oxide was utilized as the support to facilitate the NH 3 -SCR activity of FeVO 4 at low temperatures.…”
Section: Introductionmentioning
confidence: 94%
“…The introduction of niobium effectively enhances the surface acidity and alkali-resistance, thereby making niobium oxides a commonly employed modifier for facilitating the NH 3 -SCR reaction. 21 Our group previously found that the intense V–Nb–Ti interaction present in the 1V/Nb 0.15 Ti 0.85 catalyst is conducive to the low-temperature NH 3 -SCR activity. 22 Therefore, in this study, an NbTi composite oxide was utilized as the support to facilitate the NH 3 -SCR activity of FeVO 4 at low temperatures.…”
Section: Introductionmentioning
confidence: 94%